Análise da dinâmica de preços entre os mercados futuros de grão, farelo e óleo de soja na China e Estados Unidos - Bendinelli, Wellington Gustavo [UNESP] (2014)
The soy consumption in China exceeded domestic production capacity, especially due to the increase in consumption of oil and soybean meal, induced by income growth and population growth, particularly in large urban areas. As a rapid response to soaring demand, China began importing soybean mainly from three countries: USA, Brazil and Argentina. With this change in the pattern of consumption, byproducts of industrialization of soybean, the oil and the meal, have gained importance in the everyday life of the Chinese population. Soybean meal came to be used in animal feed, and soybean oil replaced the consumption of rapeseed oil for human consumption. Thus, the aim of this study was to analyze the relatio nships of causal and of transmission of prices of grain, meal and soybean oil in China and in the United States. Data are referring to the period from January 2006 to October 2013, with a daily periodicity of the closing prices of the products analyzed in the stock exchanges of Dalian and Chicago. It was used the causality methodology of Granger to test the relationships between the variables and it were applied vector autoregression models with error correction model (ECM). The empirical results indicate t he existence of a relationship of long - run equilibrium in the levels of future prices between the analyzed markets, identifying the incorporation of the same information in the price formation process. So, the possibility of arbitration between these marke ts is reduced wit